(untitled) (Research, Society and Development, 2023)
The regional agriculture secretariat is a body responsible for providing assistance to rural producers, disseminating knowledge and contributing to the development of policies aimed at the product sector, promoting and disseminating the municipality’s potential and, acting in the inspection and trade of products from agriculture and livestock municipal. The objective of the study was to describe the attributions of the municipal secretary of agriculture of Ipubi-PE, focusing on the support to the farmers and, mainly, in the supervision of the activities carried out in the municipal public slaughterhouse. The activities carried out at the municipal agriculture department of Ipubi-PE and at the municipal public slaughterhouse were monitored from April 5 to June 23, 2021, totaling 330 hours. During this period, 687 animals were slaughtered, and the main causes of condemnation were contusion, pregnancy, exhaustion and low body condition score presented by the animal. From the follow-up of activities with the secretary of agriculture of the municipality of Ipubi -PE, it was observed that maintaining quality and human food safety has been a major challenge in the meat production chain. It is possible to assess the importance of preventing zoonoses transmitted by food, as well as the health education that producers must adopt.